Preclinical evaluation of the PI3K/Akt/mTOR pathway in animal models of multiple sclerosis - Mammana, Santa; Bramanti, Placido; Mazzon, Emanuela; Cavalli, Eugenio; Basile, Maria S.; Fagone, Paolo; Petralia, Maria Cristina; McCubrey, James Andrew; Nicoletti, Ferdinando; Mangano, Katia (My University, 2018)
The PI3K/AKT/mTOR pathway is an intracellular signalling pathway that regulates cell activation. proliferation, metabolism and apoptosis. Increasing body of data suggests that alterations in the PI3K/AKT/mTOR pathway may result in an enhanced susceptibility to autoimmunity. Multiple Sclerosis (MS) is one of the most common chronic inflammatory diseases of the central nervous system leading to demyelination and neurodegeneration. In the current study, we have firstly evaluated in silico the involvement of the mTOR network on the generation and progression of MS and on oligodendrocyte function, making use of currently available whole-genome transcriptomic data. Then, the data generated in silico were subjected to an ex-vivo evaluation. To this aim, the involvement of mTOR was validated on a well-known animal model of MS and in vitro on Th17 cells. Our data indicate that there is a significant involvement of the mTOR network in the etiopathogenesis of MS and that Rapamycin treatment may represent a useful therapeutic approach in this clinical setting. On the other hand, our data showed that a significant involvement of the mTOR network could be observed only in the early phases of oligodendrocyte maturation, but not in the maturation process of adult oligodendrocytes and in the process of remyelination following demyelinating injury. Overall, our study suggests that targeting the PI3K/mTOR pathway, although it may not be a useful therapeutic approach to promote remyelination in MS patients, it can be exploited to exert immunomodulation, preventing/delaying relapses, and to treat MS patients in order to slow down the progression of disability.